Lifelong learning theoretical and practical perspectives on adult numeracy and vocational mathematics - Fitzsimons, Gail E. (Education in a competitive and globalizing world, 2010)
Technology plays a dual role in the teaching and learning of mathematics/numeracy for adults. This book illustrates how electronic technologies offer improved levels of learning, especially in the field of mathematics.